GLOBAL WARMING PHENOMENON IN PIAAC FRAMEWORK-BASED E-MODULE: SUSTAINABLE SCIENCE LEARNING TOOL FOR SENIOR HIGH SCHOOL STUDENTS IN PALEMBANG - Alshah, Putri Herdiyanti; Saparini, Saparini; Kurdiati, Lintang Auliya; Andriani, Nely (Jurnal Pendidikan Matematika dan IPA, 2025)
This study aims to develop a valid and practical PIAAC Framework-based Learning E-Module on global warming material for senior high school. This E-Module is designed not only to convey knowledge about global warming, but also to train literacy, numeracy, and problem solving which are very important in the 21st century. This study used the development research approach by following the flow of the Rowntree Development model and using Tessmer's formative evaluation stages, namely self-evaluation, expert review, one-to-one evaluation, and small group evaluation. The evaluation results show that the E-Module obtained a validity score of 97.96% from the expert, which is included in the very valid category. In addition, the results of one-to-one evaluation and small group evaluation showed a score of 91% and 90.77%, which is included in the very practical category. This research is expected to make a positive contribution in learning about global warming and increasing students' awareness of environmental issues, as well as providing flexible learning alternatives that can be accessed through digital devices.